Implementation of Bilingual Education in Senior High School in Indonesia: A Literature Review - Natasya Sugara, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Indonesia is a country with diverse cultures and languages. Not only does it use Indonesian as the national language, but it also consists of a variety of regional languages, which are numerous in Indonesia. Even just different villages have different languages. Mastering the language will support success in school. Bilingual learning is very good at the senior high school level. Because the knowledge needed to organize bilingual programs is still lacking. The aim of this research is to find out how bilingual education is implemented in senior high schools, especially in Indonesia. Data was collected through references to previous relevant journals related to bilingualism in senior high school education in Indonesia. This research uses qualitative descriptive or literature review. In this research, theories and opinions are the result of a study of scientific articles and scientific journals that are relevant to this research. The implementation of bilingual education programs can be encouraged by three supporting objects in high school, namely; (1) The Teachers’ English, (2) The Students’ English and (3) The staffs’ English.